The 10-20-30 training concept improves performance and health profile in moderately trained runners - Gunnarsson, T. P.; Bangsbo, J. (Journal of Applied Physiology, 2012)
The effect of an alteration from regular endurance to interval (10-20-30) training on the health profile, muscular adaptations, maximum oxygen uptake (VO2max), and performance of runners was examined. Eighteen moderately trained individuals (6 females and 12 males; VO2max: 52.2 ± 1.5 ml/kg·min) (means ± SE) were divided into a high-intensity training (10-20-30; 3 women and 7 men) and a control (CON; 3 women and 5 men) group. For a 7-wk intervention period the 10-20-30 replaced all training sessions with 10-20-30 training consisting of low-, moderate-, and high-speed running (<30%, <60%, and >90% of maximal intensity) for 30, 20, and 10 s, respectively, in three or four 5-min intervals interspersed by 2 min of recovery, reducing training volume by 54% (14.0 ± 0.9 vs. 30.4 ± 2.3 km/wk) while CON continued the normal training. After the intervention period V?o2max in 10-20-30 was 4% higher, and performance in a 1,500-m and a 5-km run improved (P < 0.05) by 21 and 48 s, respectively. In 10-20-30, systolic blood pressure was reduced (P < 0.05) by 5 ± 2 mmHg, and total and low-density lipoprotein (LDL) cholesterol was lowered (P < 0.05) by 0.5 ± 0.2 and 0.4 ± 0.1 mmol/l, respectively. No alterations were observed in CON. Muscle membrane proteins and enzyme activity did not change in either of the groups. The present study shows that interval training with short 10-s near-maximal bouts can improve performance and VO2max despite a ~50% reduction in training volume. In addition, the 10-20-30 training regime lowers resting systolic blood pressure and blood cholesterol, suggesting a beneficial effect on the health profile of already trained individuals.